PKM PENGUSAHA TAHU DESA SUMBEREJO WETAN KECAMATAN NGUNUT KABUPATEN TULUNGAGUNG - Agussalim Adriansyah; Edi Sudiarto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The establishment of this tofu business aims to meet the daily needs of partners and in the future to create broader employment opportunities for the people of Sumberejo Kulon Village in particular and the Tulungagung community in general.Problems faced by partners related to the production process are soybean grinding equipment which currently still uses soybean grinding services in neighboring partners so that they have to pay fees for grinding services, soy cooking equipment that is already unfit for cooking, less clean production sites, and very knowledge limited to bookkeeping and managing their business. The PKM (Community Partnership Program) program is expected to be able to solve the problems faced by partners so that it will create a larger and more efficient tofu business so that in the future it can strengthen the national economy.